An assessment of lung volumes and gas transfer in sickle-cell anaemia - Miller, G. J. (1971)
Lung volumes, gas transfer, and anthropometry were assessed in sickle-cell anaemia in 13 patients with previous pulmonary episodes and 12 without this history. Respiratory symptoms were assessed with a standard questionnaire, total lung capacity and its subdivisions, the carbon monoxide transfer factor (TF), diffusion capacity of the alveolar capillary membrane (Dm), and the alveolar capillary blood volume (Vc) were measured, and stature, sitting height and chest diameters were recorded. Total lung capacity and vital capacity were reduced because the thorax was small relative to body size in these patients. TF was reduced by anaemia, small lungs, and a low Dm which was not simply a consequence of small lungs. This reduction tended to be offset by an increase in Vc. The cause of the reduction in Dm above that due to small lungs was probably located in the pulmonary circulation. Anaemia was considered unlikely to be responsible, and although a difference between the reactivity of carbon monoxide with Hb A and Hb S may have contributed to the reduction in Dm and the increase in Vc, it was thought unlikely to be the only cause: Dm was significantly lower in patients with a history of pulmonary complications and in non-smokers than in those without this history and in smokers. Alveolar capillary collapse or occlusion may also have reduced Dm in sickle-cell anaemia and accounted for the greater reductions in those with previous pulmonary episodes and in non-smokers.